Study on Pressure Relief Technology of High-Pressure Water Jet of Residual Coal Pillar in Overlying Goaf in Close Seam Mining - Shang Yang; Xuehui Li; Jun Wang; Shuhao Yang; Zhen Shen; Guangzheng Xu (Shock and Vibration)
To solve the problem of strong ground pressure behaviour under a residual coal pillar in the overlying goaf of a close-distance coal seam, this paper proposes the technology of weakening and relieving the residual coal pillar in the overlying goaf by a high-pressure water jet. Based on the geological occurrence of the No. 3 coal seam and mountain No. 4 coal seam in the Yanzishan coal mine, the high-pressure water jet pressure relief technology of residual coal pillars in the overlying goaf of close-distance coal seams was studied by theoretical analysis and field industrial tests. First, the elastic-plastic zone of the residual coal pillar and the stress distribution law of the floor are obtained by theoretical analysis, and the influence degree of the residual coal pillar on the support of the lower coal seam working face is revealed. Then, a high-pressure water jet combined with mine pressure is proposed to weaken the residual coal pillar. Finally, through the residual coal pillar hydraulic cutting mechanical model and “double-drilling double-slot” model, the high-pressure water jet drilling layout parameters are determined, and an industrial field test is carried out. The single knife cutting coal output and 38216 working face hydraulic support monitoring data show that high-pressure hydraulic slotting can weaken the strength of the coal body to a certain extent, destroy the integrity of the residual coal pillar, cut off the load transmission path of the overlying strata, and reduce the working resistance of the hydraulic support under the residual coal pillar to a certain extent, which is beneficial to the safe mining of the working face.